Integrating Banjar Cultural Values into Premarital Counseling: A Randomized Controlled Trial on Marital Readiness in Indonesia - Jarkawi, Jarkawi; Handayani, Eka Sri; Hayati, Sri Ayatina; Haryadi, Rudi; Ridhani, Akhmad Rizkhi; Hasby, Nazar; Puteri, Nur Ananda (citeus, 2025)
Marriage readiness is a critical factor in ensuring long-term relationship satisfaction and resilience. In Indonesia, challenges such as rising cases of domestic violence and marital instability highlight the urgent need for more effective premarital counseling programs. However, existing interventions often lack cultural sensitivity, particularly in multicultural societies like Indonesia, which encompasses over 300 ethnic groups. This study examines the effectiveness of a culturally-informed premarital counseling program based on Banjar marital customs in enhancing marital readiness. A randomized controlled trial (RCT) was conducted with 32 engaged individuals divided into an experimental group receiving Banjar-based counseling and a control group participating in the government’s standard premarital counseling. The marriage readiness scale was used to measure psychological preparedness across domains such as communication, financial management, parenting, and lifestyle adjustments. Statistical analysis using the Mann-Whitney U test revealed significant improvements in the experimental group (U = 16.000, Z = -5.899, p < 0.001) compared to the control group. The findings underscore the importance of integrating local cultural values into premarital counseling to enhance mental readiness for marriage. By fostering deeper connections to cultural traditions, the intervention promoted mutual respect, emotional maturity, and role preparedness among participants. This study contributes to the growing discourse on culturally-informed psychosocial interventions and offers a scalable model for multicultural societies across Asia and beyond.